The Relationship between Mechanical Properties and Gradual Deterioration of Microstructures of Rock Mass Subject to Freeze-thaw Cycles (2018)
Under freeze-thaw cycles, the relationship between rock microstructure deterioration and its macroscopic mechanical characteristics has drawn extensive attention from engineers. With the objective to incorporate freeze-thaw cycle experiment into headrace tunnel engineering, in the present study two groups of andesite rock samples in different states are tested under the conditions of the lowest freezing temperature of –40 ℃ and the thawing temperature of 20 ℃. Damage detection was performed by magnetic resonance imaging for the interior microstructure of rock samples subject to different freeze-thaw cycles, and the relationship between the sample mechanical properties and gradual deterioration of rock microstructures was discussed. The results demonstrate evident influence of freeze-thaw cycle on the damage and deterioration of internal pore structure in andesite, and the rock uniaxial compressive strength and elasticity modulus exhibit a decreasing trend with the increase of freeze-thaw cycles. After 40 cycles, the strength of naturally saturated rock samples decreases by 39.4% (equivalent to 69.4 MPa) and the elasticity modulus drops by 47.46% (equivalent to 3.27 GPa). For rock samples saturated by vacuum, 40 freeze-thaw cycles lead to a decrease of 36.86% (equivalent to 58.2 MPa) in rock strength and a drop of 44.85% (equivalent to 2.83 GPa) in elasticity modulus. Therefore, the test results quantitatively elucidate the substantial influence of freeze-thaw cycle on the damage and deterioration of internal structure in andesite.